Post treatment improvement of laryngopharyngeal reflux diagnosed using a novel algorithm: A cohort study - Nukusbekova, Gulnur; Toguzbayeva, Dinara; Oguz, Haldun; Hashemi, Ramil; Taukeleva, Saule; Daniyar, Kaldybayev; Karibayeva, Indira (Acta Biomedica Atenei Parmensis, 2024)
Purpose: to compare pre and post treatment measurements in patients with laryngopharyngeal reflux diagnosed, to patients gastroesophageal reflux disorder and without symptoms of laryngopharyngeal reflux using combined algorithm. Methods: This prospective cohort study involving 384 patients was conducted. We used the following algorithm: the reflux symptom index (RSI) questionnaire score of >13; videolaryngastroboscopy with the assessment of the reflux finding score (RFS)>7; pH-strips of mucus from the laryngopharynx; acoustic analysis of the voice of singers with voice disorders. Patients with LPR and GERD were treated with proton pump inhibitors (PPIs) at a dose of 20 mg twice a day, and recommendations for lifestyle and dietary changes were given for a month. Patients were monitored for a period of six months.Results: After treatment, RSI and RFS results in patients with LPR and GERD significantly improved from 19.9±6.4 & 9.1±1.7 and 18.7±5.3 & 10.10±2.4 respectively (p˂0.001). In patients without the symptoms of LPR, the laryngopharyngeal medium pH ranged from min 5.5 to max 7.5, and in cases of suspected LPR and GERD, it ranged from min 5 to max 8 and min and 4.5 to max 8.5 respectively. The acoustic voice analysis scores changed after therapy, p-value˂0.05.Conclusion: The lack of a gold standard and the inaccessibility of diagnostic methods make LPR diagnosis a very complex task. However, using the proposed diagnostic algorithm, the post treatment scores were improved. More studies are needed to validate the     algorithm for early diagnosis of LPR.